PENGARUH PENGUNGKAPAN SUKARELA MANAJEMEN RISIKO NON-KEUANGAN TERHADAP NILAI PERUSAHAAN SEKTOR CONSUMER NON-CYCLICALS YANG TERDAFTAR DI BURSA EFEK INDONESIA - Adiyat Imaduddin; Imam Ghozali (Diponegoro Journal of Accounting, 2022)
This study aims to examine the effect of voluntary risk management disclosure on firm value in the Consumer Non-Cyclicals sector listed on the Indonesia Stock Exchange (IDX) for the 2019 period. In addition, this study also examines more complete and broad disclosures from companies are able to minimize information asymmetry for investors in making investment decisions. Based on signal theory, which is related to information asymmetry, companies that disclose more information will have high firm value as well.The population in this study were companies in the Consumer Non-Cyclicals sector for the 2019 period with a total sample of 75 out of 81 populations listed on the Indonesia Stock Exchange (IDX). This study uses multiple regression analysis as an analytical tool.The results showed that the voluntary disclosure of operating risk management, strategic risk management, and empowerment risk management had a positive and significant effect on firm value. Meanwhile, voluntary disclosure of integrity risk management and information technology processing risk management has no effect on firm value. Based on these results, it can be said that wider voluntary risk management disclosure of operating risk, strategic risk, and empowerment risk will increase the value of the company in the investor's perspective, while the ineffectiveness of voluntary risk management disclosure of integrity risk and information technology processing risk may be influenced by several other factors.